Factors affecting local plant knowledge in isolated communities from Patagonian steppe: Metacommunity theory is revealed as a methodological approach - Rosa Santoro, Flávia (2022)
The Patagonian steppe is a refuge for several indigenous peoples who live in relatively isolated communities, depending heavily on natural resources for their activities, health, and food security. The local ecological knowledge is a reservoir that generates full wellbeing and for which it must be the object of protection and local development. In this study, we aimed to find which factors can influence local ecological knowledge from a metacommunity on the Patagonian steppe. We analyzed variation in knowledge about cultivated and gathered plants used as medicinal, edible, and firewood according to multiple factors widely discussed in the ethnobiological literature: age, gender, formal education, occupation, indigenous identity, contact with urban centers, use of biomedicine, hunting, and handcrafted textile production. We conducted semi-structured interviews with local experts, accessed by the snowball technique. We found that formal education is a key factor in the variation of local ecological knowledge among people. In addition, we found that knowledge varies between people who practice activities inside and outside the home, concentrating knowledge between cultivated and gathered plants, respectively. Our urbanization proxies did not point to an influence of this factor on local knowledge, but specialists living in a larger community with signs of internal urbanization processes had much less knowledge. Our results allowed us to visualize the importance of studying metacommunities as a whole, to verify complexities and intersections of overlapping factors. Studies in metacommunities open up a range of possibilities for ethnobiological analysis.